THE CORRELATION OF PREPOSITIONS AND PREPOSITIONAL PHRASE FORMATION MASTERY WITH IDENTIFY THE PREPOSITIONAL PHRASE IN DESCRIPTIVE TEXT ABILITY AT THE STUDENTS OF SMK STATE 1 SUKADANA ACADEMIC YEAR 2012/2013 - Siskan Hasbid; Fenny Thresia (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2013)
This research is attended to find out about the correlation of prepositions and prepositional phrase formation mastery with identify the prepositional phrase in descriptive text ability at the students of SMK state 1 Sukadana academic year 2012/2013. This research is a quantitative research with correlation design by correlating three variables. The independent variable of this research is prepositions and prepositional phrase formations while the dependent variable is identify the prepositional phrase in descriptive text ability. The population of this research is the students at tenth grade of TKJ 1 class of SMK N 1 Sukadana academic year 2012/2013. The number of the students is about 240 divide into six classes and each class severally consists of 40 students. The research took the sample by using purposive sampling technique. The samples of the research were 40 students. The data collecting method is done by using instrument test in each variable. The research used some analyzes data. The first to know there is correlation between X1 with Y, the researcher used bivariate correlation. It got rscore = 0,996 > rtable = 0,312. It means that there is positive significant correlation. The first to know there is correlation between X2 with Y, the researcher used bivariate correlation. It got rscore = 0,841 > rtable = 0,312. It means that there is positive significant correlation. The first to know there is correlation between X1, X2 and Y simulationsly, the researcher used multivariate correlation test. This fact can be proven by the result of the ro = 0,9995 > rtable = 0,312. It means that there is very high positive significant correlation Based on theoritycal review and the finding result of the data, it can be concluded that, in this research there is very high significant correlation of prepositions and prepositional phrase formation mastery with identify the prepositional phrase in descriptive text ability at the students of SMK State 1 Sukadana academic year 2012/2013.